Uložení rotorů turbodmychadel na valivých ložiscích - Šárovec, Marek (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2017)
Cílem této diplomové práce je navrhnout uložení rotoru turbodmychadla na valivých ložiskách. Diplomová práce se skládá ze dvou rešeršních kapitol zabývajících se rotorem turbodmychadla a výpočtem valivých ložisek. V další kapitole je popsána aplikace na konkrétním případě rotoru za pomoci multi body systemu Adams – View. V závěrečné kapitole jsou srovnány výsledky rotoru uloženého na ložiskách s ocelovými a keramickými valivými elementy. Dále pak srovnání valivých ložisek s kluznými ložisky, z čehož vyplývá, že díky valivým ložiskům došlo ke snížení ztrátového výkonu při maximálních otáčkách o více než 50 %.

The main purpose of this diploma thesis is to design turbocharger rotor using rolling element bearings. The diploma thesis is compiled from two specialized search parts dealing with turbocharger rotor and rolling element bearing computation, respectively. The application of the particular rotor using the multi body system Adams – View is described in the following chapter. In the last chapter, one can find the comparison between rotor using bearing with steal and hybrid ceramic rolling element. Also, there is compariosn between rolling element bearing and journal bearing. In the maximum rotor speed, the decrease of more than 50 % in power loss, due to usage of rolling element bearing, resulted from this comparison.
Turbocharger Rotors using Rolling Bearings
Keywords: Turbodmychadlo; rotor; valivá ložiska; tuhost; multi body system; Turbocharger; rotor; rolling element bearing; stiffness; multi body system